Simplify the Following Expression: 35 + (–13) + (+8) – (–6).


Question: Simplify the following expression: 35 + (-13) + (+8) - (-6).

The question is based on the operation of integers.

Answer: 35 + (-13) + (+8) - (-6) = 36

Let's use the rule of subtraction of integers to solve: 35 + (–13) + (+8) – (–6)

Explanation:

The rules for multiplication involving + and - are given by:

  • (+) × (+) = + 
  • (+) × (-) = -
  • (-) × (+) = -
  • (-) × (-) = +

Therefore, 35 + (-13) + (+ 8) - (-6) = 35 - 13 + 8 + 6 = 35 + 8 + 6 - 13 = 36

Thus, by simplifying the given expression: 35 + (–13) + (+8) – (–6) we get 36.